Investment Audit in Ensuring the Development of Enterprises of Public Interest - Fedorov Ihor O.; Nezhyva Mariia O. (Bìznes Inform, 2023)
Determining the efficiency of activity and investment potential of public interest enterprises for the purpose of further investment can be carried out in different ways, one of which is conducting an independent investment audit. The aim of the article is to present the effect of the investment audit of enterprises of public interest in ensuring their development and assessing the real efficiency of investments, as well as establishing the further vector of its development. The article summarizes the state and development strategy of the investment audit of public interest enterprises. The content of the existing investment audit procedures and the directions of further development are disclosed, the views of scientists on the development of the subject area of knowledge and practical activity are systematized. The market of auditing services for the performance of tasks for enterprises of public interest has been analyzed, the main problems characteristic of the domestic market of auditing services have been identified. The concept of "investment audit" is substantiated, its purpose and tasks are defined. Its main elements are formulated and approaches to improving the methodology are proposed according to the stages of conducting an investment audit of the activities of enterprises of public interest. Conducting an investment audit will contribute to ensuring the development and increasing the investment attractiveness of the enterprise among users who need complete, reliable, unbiased and timely information from independent experts as a basis for making investment decisions.